Estimation of damping through internally excited roll tests. (15th July 2018) - Oliva-Remola, Adriana; Bulian, Gabriele; Pérez-Rojas, Luis
Abstract: Roll damping represents a key factor for a proper estimation of the ship behaviour in a seaway. However, due to the typical dominance of viscous effects, accurately estimating roll damping is a challenging task. The most common experimental approach for determining roll damping parameters is based on the analysis of roll decays, although forced and excited roll tests in calm water or in waves have been used as well. This paper proposes a technique for estimating roll damping from internally excited roll tests in calm water. Tests are performed by exciting roll motion through an internal shifting mass. Roll damping parameters can then be determined from the analysis of the obtained roll response curves. The paper describes the experimental technique and a nonlinear mathematical model for representing the system dynamics. A procedure is proposed for determining roll damping coefficients, using, as a basis for the analysis, the developed mathematical model. A case study is reported where damping coefficients are determined for a trawler fishing vessel using the proposed technique. Obtained results are compared with those from standard roll decays analysis. For model validation purposes, the experimental roll response curves are also compared with those simulated through the developed mathematical model. Highlights: Determination of nonlinear roll damping through internally excited roll tests in calm water. Development of nonlinear models of roll dynamics considering excitation from internal moving mass. Description of a procedure for the analysis of experimental data. Case study: roll damping determination and model validation for a trawler fishing vessel. Comparisons of roll damping from proposed procedure and from roll decays.